PENGEMBANGAN ALAT EVALUASI MENGGUNAKAN WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SD NEGERI 2 SEULALAH - Wahyuni, Siti; Sukirno; Mulyahati, Bunga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of learning evaluation that is still carried out conventionally tends to make students less interested and less active during the learning process. This condition also affects the implementation of evaluations that require a relatively longer time and provide less engaging learning experiences for students. This study aimed to determine the feasibility, practicality, and effectiveness of a Wordwall-based evaluation tool on the topic of characteristics of living things for third-grade students at SD Negeri 2 Seulalah. This study employed a Research and Development (R&D) method using the ADDIE development model consisting of Analyze, Design, Development, Implementation, and Evaluation stages. The research subjects consisted of 23 third-grade students of SD Negeri 2 Seulalah. Data collection techniques included observation, interviews, questionnaires, documentation, and learning outcome tests. The results indicated that the developed Wordwall-based evaluation tool met the criteria of validity, practicality, and effectiveness. The results of expert validation I increased from 47% to 56% and reached the highly feasible category at the final stage, while expert validation II increased from 77% to 97% with a highly feasible category. The practicality results obtained a percentage of 85% from teachers and 83.43% from students. In addition, the effectiveness results showed an increase in the average pre-test score from 52.17 to 90 in the post-test. Therefore, the Wordwall-based evaluation tool can be used as an alternative learning evaluation tool that supports improving student learning outcomes. Keywords: evaluation tools, Wordwall, learning outcomes, IPAS